Market allocations under ambiguity: A survey - Antoine Billot; Sujoy Mukerji; Jean-Marc Tallon (Queen Mary University of London, School of Economics and Finance, 2019)
We review some of the (theoretical) economic implications of David Schmeidler's models of decision under uncertainty (Choquet expected utility and maxmin expected utility) in competitive market settings. We start with the portfolio inertia result of Dow and Werlang (1992), show how it does or does not generalize in an equilibrium setting. We further explore the equilibrium implications (indeterminacies, non revelation of information) of these decision models. A section is then devoted to the studies of Pareto optimal arrangements under these models. We conclude with a discussion of experimental evidence for these models that relate, in particular, to the implications for market behaviour discussed in the preceding sections.
Keywords: D81; 330; Choquet Expected Utility; Maxmin Expected Utility; No-trade; Risk Sharing; Indeterminacy; Experimental evidence